Increased adrenomedullin levels in nontraumatic septic patients - (:unkn) unknown (My University, 2005)
Aim. The study objective was to assess plasma Adrenomedullin (ADM) levels in patients with nontraumatic sepsis. Also we investigated plasma ADM levels as a marker for early detection and evaluation of the severity of sepsis. Methods. We measured plasma ADM levels in 49 nontraumatic various forms of septic patients and 42 healthy volunteers serving as controls. Results. Plasma levels of ADM in patient group (150.38±99.60 fmol/ml) was significantly higher than that of controls (8.07±5.52 fmol/ml). In spite of the difference between the patient group and controls, no correlation was found between the severity of sepsis and plasma ADM levels. Also plasma ADM levels were not different between the sources of sepsis. Conclusion. The plasma ADM levels are markedly increased in septic patients with different sources of infections, probably due to either decreased clearance or increased synthesis by the affected organs but the source of infection does not have an effect on this increase.
Keywords: Adrenomedullin; Sepsis